Sprachliche Aggression bei Martin Luther Argumentationsformen und -funktionen am Beispiel der Streitschrift Wider das Papsttum zu Rom vom Teufel gestiftet (1545) - Hundt, Markus (Lingua Historica Germanica, 2022)
Martin Luther was not just a great reformer and bible translator, but also an extremely pugnacious and, in his argumentation, sometimes polemical contemporary. This form of linguistic aggression is very clearly expressed in his pamphlet "Against the Papacy of Rome, Founded by the Devil" of 1545. This volume reveals the linguistic means that he used to implement this by undertaking a practical argumentation analysis.